2010
DOI: 10.1002/jso.21447
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic agents and late anastomotic complications

Abstract: Anticancer agents targeting circulating vascular endothelial growth factor (VEGF) (e.g., bevacizumab and aflibercept) are strong angiogenesis inhibitors. As such, they may hamper the healing process, notably in the early postoperative period. Whether antiangiogenic agents may be associated with late postoperative healing complications is less known. We reviewed three cases of patients with anastomotic complications under antiangiogenic treatment occurring more than 1 year after initial surgery and we conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 19 publications
0
26
1
6
Order By: Relevance
“…[8]. Das zeigt, dass der Prozess der Neoangiogenese bei vollständig erholter mechanischer Stabilität der Anastomose noch relativ lange von großer Bedeutung ist.…”
Section: E Einer Der Wichtigstenunclassified
“…[8]. Das zeigt, dass der Prozess der Neoangiogenese bei vollständig erholter mechanischer Stabilität der Anastomose noch relativ lange von großer Bedeutung ist.…”
Section: E Einer Der Wichtigstenunclassified
“…In contract, Deshaies et al [4] reported on 18 cases of unusually delayed anastomotic complications in patients receiving bevacizumab after gastrointestinal surgery with the anastomotic complication occurring between 3 and 78 months after surgery (mean, 18 months). This data supports our report of 41 months between surgery and wound dehiscence.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a single case of Fournier gangrene in a man during bevacizumab treatment has been reported; it happened 4 months after chemotherapy with 5-fluorouracil/leucovorin/oxaliplatin for advanced colorectal cancer [40]. In a review of the literature, late anastomotic complications attributable to the use of anti-angiogenetic agents amounted altogether to 18 cases [16]. It is noteworthy that they happened very late, >12 or even 78 months after treatment with bevacizumab.…”
Section: Discussionmentioning
confidence: 99%
“…Despite few recommendations for its administration 6 weeks before or 4 weeks after surgery [9,10], there is still no clear evidence in current clinical practice with respect to the optimal administration time point. On the other hand, in a few studies, complications attributed to bevacizumab administration [11,12,13,14,15] have been reported in cancer patients, especially late anastomotic complications [16]. In an experimental setting, only studies investigating the effect of locally applied bevacizumab on corneal wound healing in rats, mice and rabbits have been reported [17,18,19,20,21], although with conflicting results.…”
Section: Introductionmentioning
confidence: 99%